Rings in the esophagus are not always eosinophilic esophagitis: Case series of ring forming lymphocytic esophagitis and review of the literature - Pleet, Julia L.; Taboada, Sofia; Rishi, Arvind; Milman, Perry J.; Trindade, Arvind J. (Endoscopy International Open, 2017)
Background and study aims Lymphocytic esophagitis (LyE) is a form of chronic esophagitis characterized by edema and lymphocytic infiltration of the epithelial peripapillary fields, without eosinophils. Its significance is unclear, as it was previously thought to have little clinical impact. More recent literature, however, describes a paradigm shift suggesting a distinct entity. We report on 3 patients with dysphagia who were found to have esophageal rings on endoscopy. Histology was consistent with LyE. Additional features reported in this cohort included an esophageal web, esophageal pseudodiverticula and esophageal erythema. We also report a current literature review of the topic. The literature review reported here includes another 37 patients with LyE and rings, for a total of 40 patients. Patients with LyE may present with esophageal rings and other findings. LyE should be considered in the differential diagnosis of esophageal rings.